KEBERADAAN REGULASI DESAIN INDUSTRI BERKAITAN DENGAN PERLINDUNGAN HUKUM ATAS KARYA DESAIN DI BALI - SUPASTI DHARMAWAN, NI KETUT; MAS ARYANI, NYOMAN (Kertha Patrika, 2012)
Effectiveness of Industrial Design registration provision based on Act No. 31, 2000 concerning IndustrialDesign in Bali has not been fully enforced. It was caused by some factors such as: lack of understanding ofIndustrial Design in societies and some of them do not know the existence of this regulation which regulate thefirst file system, some societies who has not developed the need to have laws on Industrial Design as well as thepresence of communal cultures of the Indonesian people, which is completely different from the basic concept ofindividual right protection of IPR, which based on legal cultures of west countries have contributed to thedifficulties in fully implementing IPR. The other factors caused by lack of awareness Industrial Design protectionboth the substance and the existence of this provision among law enforcers and the inadequate infrastructurerequired to administer IPR.. The concept protection of Industrial Design protect designer / owner or recipient ofthe right who register their right based on first to file system. Through this system the designer would have anexclusive rights in the form of economic and moral right. The legal consequence of the inefficiency in enforcingarticle 10 jo article 12 of the Act No. 31 of 2000 concerning Industrial Design , which regulate first to file, mightresult in the failure of the designer to secure their right over their designs, whereas the legal protection shall be goto the person who registers and have evident in form of certificate registration.
Keywords: The provision of Industrial Design, law enforcement of Industrial Design, legal protection of Industrial Design, the legal conscience of first to file system